A Legal Analysis of Children's Personal Data Protection in AI-Based Education Platforms in Indonesia - Halek Mu’min; Andri Herman Setiawan; Eko Siswo Adi Sahputra (Politeknik Siber Cerdika Internasional, 2026)
This study aims to analyze the protection of children's personal data in artificial intelligence (AI)-based educational platforms in Indonesia through a normative juridical approach using a statutory approach, a conceptual approach, and a comparative approach to GDPR-K, COPPA, and the AI ​​Act. The research focuses on legal regulations related to children's data, the implementation of protection by AI-based EdTech platforms, the risk of child data misuse, and the adequacy and effectiveness of national regulations. The results of the study indicate that although Indonesia has a Personal Data Protection Law as the main legal framework, the regulation does not yet provide specific protection for children's data, especially regarding automatic profiling, verification of parental consent, algorithmic audits, and restrictions on data use for commercial purposes. Comparison with international standards also shows that Indonesian regulations are still general and do not meet the principle of preventive protection that is characteristic of global regulations. This study concludes the need to develop derivative regulations related to children's data, technical guidelines for data processing by AI, and the establishment of an effective oversight mechanism to minimize the risk of data misuse and ensure the fulfillment of the principle of the best interest of the child in the digital education ecosystem.